Impact of Bep or Carboplatin Chemotherapy on Testicular Function and Sperm Nucleus of Subjects with Testicular Germ Cell Tumor - Ghezzi, Marco; Berretta, Massimiliano; Bottacin, Alberto; Palego, Pierfrancesco; Sartini, Barbara; Cosci, Ilaria; Finos, Livio; Selice, Riccardo; Foresta, Carlo; Garolla, Andrea (Frontiers in Pharmacology, 2016)
Young males have testicular germ cells tumours (TGCT) as the most common malignancy and its incidence is increasing in several countries. Besides unilateral orchiectomy (UO), the treatment of TGCT may include surveillance, radiotherapy or chemotherapy (CT), basing on tumour histology and stage of disease. It is well known that both radio and CT may have negative effects on testicular function, affecting spermatogenesis and sex hormones. Many reports investigated these aspects in patients treated with bleomycin, etoposide and cisplatin (BEP), after UO. In contrast no data are available on the side effects of carboplatin treatment in these patients. We included in this study 212 consecutive subjects who undergone to sperm banking at our Andrology and Human Reproduction Unit after UO for TGCT. Hundred subjects were further treated with one or more BEP cycles (BEP-group), 54 with carboplatin (Carb group) and 58 were just surveilled (S-group). All patients were evaluated for seminal parameters, sperm aneuploidy, sperm DNA, sex hormones, volume of the residual testis at baseline (T0) and after 12 (T1) and 24 months (T2) from UO or end of CT. Seminal parameters, sperm aneuploidies, DNA status, gonadic hormones and testicular volume at baseline were not different between groups. At T1 we observed a significant reduction of sperm concentration and sperm count in the BEP group versus baseline and versus both Carb and S- group. A significant increase of sperm aneuploidies was present at T1 in the BEP group. Similarly, the same group at 1 had altered sperm DNA integrity and fragmentation compared with baseline, S group and Carb group. These alterations were persistent after two years from the end of BEP treatment. Despite a slight improvement at T2, the BEP group had still higher percentages of sperm aneuploidies than other groups. No impairment of sperm aneuploidies and DNA status were observed in the Carb group both after one and two years from the end of treatment. Despite preliminary, these data demonstrate that in selected patients with TGCTs CT with carboplatin represents a therapeutic option that that seems to not affect sex hormones, spermatogenesis and sperm nucleus.